2020
DOI: 10.1007/s00330-020-07130-y
|View full text |Cite
|
Sign up to set email alerts
|

Radiological review of prior screening mammograms of screen-detected breast cancer

Abstract: Objective To perform a radiological review of mammograms from prior screening and diagnosis of screen-detected breast cancer in BreastScreen Norway, a population-based screening program. Methods We performed a consensus-based informed review of mammograms from prior screening and diagnosis for screen-detected breast cancers. Mammographic density and findings on screening and diagnostic mammograms were classified according to the Breast Imaging-Reporting and Data System®. Cases were classified based on visibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 28 publications
1
22
0
Order By: Relevance
“…The results from the review study are presented in two separate papers; paper 3 is presenting results from the review of the screen-detected cancers (204) and paper 4 results from the review of interval cancers (205). In this section, results from the review are discussed as a whole, independently from the papers, to visualize a broader perspective.…”
Section: Data Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…The results from the review study are presented in two separate papers; paper 3 is presenting results from the review of the screen-detected cancers (204) and paper 4 results from the review of interval cancers (205). In this section, results from the review are discussed as a whole, independently from the papers, to visualize a broader perspective.…”
Section: Data Analysesmentioning
confidence: 99%
“…No statistically significant differences were observed regarding the classification into the main categories mass, calcification, asymmetry or distortion between missed and minimal signs cancers at prior screening. With regard to further subclassification of the findings (Figure 1.11), differences applied between missed and minimal signs (204). However, this was an obvious consequence of the design, as allocation into the categories missed or minimal signs was merely based on the suspiciousness of the findings, and the different subclasses mammographic findings have different levels of suspiciousness (86).…”
Section: Missed and Minimal Signs Cancermentioning
confidence: 99%
“…Recently diagnosed cancer cases were preferred over older cases to facilitate retrieval from the picture archiving and communication systems (PACS). The review is described elsewhere [26].…”
Section: Retrospective Radiological Reviewmentioning
confidence: 99%
“…The common mammography findings in missed cancer included calcification, asymmetry, and focal asymmetry. However, mass was the most common finding in previous studies [ 18 , 19 ]. Of the included patients, 83.2% of true negative, 78.8% of minimal signs and 61.8% of missed cancer had dense breast.…”
Section: Discussionmentioning
confidence: 99%
“…Among the IHC types, luminal A was the most common in 16 patients (59.3%). Hovda et al reported that the estrogen receptor positivity was 95% (215/234) in missed cases [ 19 ]. Kim et al reported that the most common presentation in both screening and symptomatic groups was luminal A (63.6% and 54.3%, respectively) [ 22 ].…”
Section: Discussionmentioning
confidence: 99%